Isolamento e caracterização de vírus gigantes em biomas do Brasil e Antártica - Ana Cláudia dos Santos Pereira Andrade (2019)
Giant viruses are complex members of the virosphere and in recent years several new representatives have been discovered. However, many aspects about the diversity, distribution, and interaction of these viruses with host cells remain unknown. In this work, we describe the prospection of giant viruses using several samples from Brazil and Antarctica. In total, 68 viruses were isolated which were identified by real-time PCR, electron and light microscopy (1 marseillevirus, 2 pandoravirus, 1 cedratvirus and 64 mimivirus). In addition, we have analyzed some stages of the replication cycle of two isolated viral groups: mimivirus and pandoravirus. We demonstrated that mimiviruses depend on phagocytosis and phagosome acidification for entry and uncoating step, respectively, in amoebae hosts. The mimivirus capsids morphogenesis seems to be assembled from growing lamellar structures, the genome and fibrils can be acquired simultaneously, and there is a specific area surrounding the viral factory where particles acquire the surface fibrils. Finally, defective particles can be formed even in the absence of virophages. The study of the replication cycle of pandoraviruses showed an intense cytoplasmic reorganization with formation of a large VF presenting intense recruitment of membrane. In the VF morphogenesis occurs, and this can be initiated by both ends of the particle. In the more advanced stages of the cycle, the nucleus is no longer observed and the progeny formed can be released by exocytosis and by cell lysis. Together, these results contribute to building our understanding of the diversity and replication cycle of some giant viruses.